Comparative Study of Adsorption Dynamics of Fe(II) Using Bentonite Clay and Activated Carbon - S. Dadhich, Anima; Shaik Khasim Beebi, Mrs (Asian Journal of Chemistry, 2010)
Demands for a better quality of treated effluent have led to an intensive use of adsorption process as a polishing technology. The present study was aimed at removing iron using a non-conventional adsorbent, bentonite clay and a comparison of the same with activated carbon which happens to be a conventional adsorbent. The effect of contact time. adsorbent dosage. pH and initial concentration on the kinetics of adsorption was studied. It was shown that iron removal increases with increasing contact time and becomes constant after 1 h. In case of both bentonite clay and activated carbon percentage of adsorption was found to increase with increasing adsorbent dosage. The effect of pH on removal of Fe(II) showed that % adsorption increases with inceasing pH up to a certain level; thereafter it decreases. The rate constants for removal of Fe(II) with bentonite clay and activated carbon for varying initial metal concentration showed it to be a first order kinetics. The adsorption data fitted well into Freundlich adsorption isotherm. The comparison of K, the adsorption capacity, and 1/n, the adsorption intensity, values showed that bentonite clay, a non-conventional adsorbent, is on par with activated carbon in effectively removing Fe(II) from an aqueous solution.